MANAJEMEN LABORATORIUM: MENGATASI DINAMIKA EMOSIONAL DI TEMPAT KERJA ILMIAH - Zulpadrianto, Zulpadrianto; Usdarisman, Usdarisman (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
Laboratories are complex environments, where social interactions and professional demandsblend with performance pressures and organizational hierarchies. Behind the seeminglyobjective scientific activity, there are emotional dynamics that influence individual behavior,one of which is embodied shame. Based on concepts discussed by Ruebottom and Toubiana(2024), this article explores the impact of shame on laboratory management. Internalizedshame can negatively impact laboratory dynamics by inhibiting collaboration, loweringemotional energy and creating a less productive work environment. Individuals who feelshame tend to shrink emotionally and physically, which inhibits their potential to innovate andcollaborate effectively. To address this issue, labs must create a psychologically safeenvironment, where members feel supported and free from fear to conduct experiments.Inclusive leadership that supports all groups, as well as providing opportunities for reflectionand personal growth, can help reduce internalized shame. With the right managementstrategies, laboratories can become more inclusive and supportive places, which not onlyimproves the emotional well-being of laboratory members, but also fosters scientificinnovation and better collaboration